Molecular dynamics simulations of hydrogen isotope exchange in tungsten vacancies. (December 2021) - Lindblom, O.; Ahlgren, T.; Heinola, K.
Abstract: Solute hydrogen can cause many damaging processes in the lattices of metals, such as deformation of the material, which can take place in large scales through blistering and embrittlement. Especially in nuclear fusion applications, the trapped hydrogen isotope Tritium in the reactor wall materials can pose a radiological safety hazard. Techniques for hydrogen removal from metals usually require high temperatures. However, an efficient low temperature method to remove hydrogen is the so-called isotope exchange mechanism, where one isotope is being removed from the material by replacing it by another isotope introduced in the material. The atomic scale exchange mechanism of isotope exchange has not yet been determined. In this study we use molecular dynamics simulations to provide an atomic-scale explanation to the processes related to hydrogen isotope exchange in bulk materials. The results show that the lattice mono-vacancies and small vacancy clusters, usually produced in irradiation experiments, exhibit isotope exchange at low temperatures. The isotope exchange process should also be seen in other hydrogen trapping defects with similar trapping properties as vacancies. Highlights: Tritium removal rates are greatly improved by employing isotope exchange. The isotope exchange mechanism is based on keeping defects saturated. Molecular dynamics methods are well suited for studying isotope exchange.